Myeloid-derived suppressor cells: more mechanisms for inhibiting antitumor immunity - Ostrand-Rosenberg, Suzanne (Cancer Immunology, Immunotherapy, 2010)
Myeloid-derived suppressor cells (MDSC) accumulate in most cancer patients and experimental animals with cancer. They accumulate in response to pro-inflammatory mediators and they use a variety of mechanisms to block both innate and adaptive antitumor immunity. Because of their critical role in obstructing immune responses, MDSC are a strategic obstacle to immunotherapies that require activation of the host's cell-mediated and innate immune responses. Following a brief description of the factors that induce MDSC accumulation, this article reviews two newly discovered mechanisms that MDSC use to suppress the activation of CD4⁺ and CD8⁺ T cells. The first mechanism is MDSC sequestration of cysteine, an amino acid that T cells are unable to synthesize de novo and that they require for activation. The second mechanism is MDSC-mediated down-regulation of l-selectin. T cells must have an l-selectinhigh phenotype to home to lymph nodes and inflammatory sites where they encounter antigen and are activated. By down-regulating l-selectin on T cells, MDSC perturb T cell trafficking patterns and thereby inhibit T cell activation. Given the complexity of conditions that regulate MDSC accumulation and the variety of suppressive mechanisms used by MDSC, it is essential to understand which conditions and mechanisms are dominant so MDSC accumulation and/or activity can be targeted in individual patients to minimize MDSC-induced immune suppression.